Fungal Diversity in UNIMAS central air-conditioning system: A study on FRST laboratory - Siti Mariah, Sulaiman (Universiti Malaysia Sarawak, (UNIMAS), 2018)
Fungi are ubiquitous organism that can be found everywhere, including indoor environments such as laboratory. The present study was conducted to determine the diversity of the fungi exist in the laboratory. Therefore, three medias were used for the samplings such as Cornmeal (CM), Potato Dextrose Agar (PDA) and Malt Extract Agar (MEA). Three factors were involved which are, different time of sampling, different time taken for sampling and different location of the ducts. About 78 fungal isolates were obtained from the central air-conditioning system and 17 out of 78 isolates were selected as representatives for other abundant isolates. These 17 fungal isolates were further analyzed under morphological and molecular analysis. The 17 fungi were identified as Aspergillus flavus, Aspergillus aculeatus, Aspergillus fumigatus, Hymenochaete murina, Phellinus noxius, Epicoccum sorghinum, Phlebiopsis gigantea, Penicillium citrinum, Penicillium herquei, Lophiostoma sp., Poryporales sp., Trametes maxima, Earliella scabrosa, Diaporthe sp., Collariella causiiformis., Rigidoporus vinctus and Aspergillus sydowii. There are few of these fungi are pathogenic to human health. One of it is Aspergillus flavus and it has the highest frequency of isolates obtained from the central air-conditioning system in Genetic Engineering Laboratory, UNIMAS.